2017
DOI: 10.1021/acsnano.7b03522
|View full text |Cite
|
Sign up to set email alerts
|

Doping of Graphene Nanoribbons via Functional Group Edge Modification

Abstract: We report the on-surface synthesis of 7-armchair graphene nanoribbons (7-AGNRs) substituted with nitrile (CN) functional groups. The CN groups are attached to the GNR backbone by modifying the 7-AGNR precursor. Whereas many of these groups survive the on-surface synthesis, the reaction process causes the cleavage of some CN from the ribbon backbone and the on-surface cycloisomerization of few nitriles onto pyridine rings. Scanning tunneling spectroscopy and density functional theory reveal that CN groups behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
97
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(104 citation statements)
references
References 41 publications
(101 reference statements)
3
97
2
Order By: Relevance
“…Graphene-based systems have recently been popular [107] although those doped by other non-metals have also been increasingly gaining attention. [108,109] These actually resemble the polyaromatic heterocyclic side products of organic species-releasing systems. Further, the low symmetry due to the central aromatic ring could give rise to varied surface structures due to surface chirality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Graphene-based systems have recently been popular [107] although those doped by other non-metals have also been increasingly gaining attention. [108,109] These actually resemble the polyaromatic heterocyclic side products of organic species-releasing systems. Further, the low symmetry due to the central aromatic ring could give rise to varied surface structures due to surface chirality.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the final product in this reaction is an extended planar polyaromatic system important for molecular electronics. Graphene‐based systems have recently been popular although those doped by other non‐metals have also been increasingly gaining attention . These actually resemble the polyaromatic heterocyclic side products of organic species‐releasing systems.…”
Section: Discussionmentioning
confidence: 99%
“…To date, edge‐doping methodology and the preparation of N‐doped GNRs have been widely witnessed . Recently, Pascual's group designed the precursor by functionalizing the edge with nitrile groups . As a result, N‐doped GNRs ( Figure a) formed through the stepwise on‐surface synthesis stages.…”
Section: Doping Gnr With Heteroatomsmentioning
confidence: 99%
“…For instance, molecule 10 with an added phenyl substituent in molecule 1 is designed to fabricate yield (shown in Figure a) and, experimental STS spectra has demonstrated that its band gap is 1.0 eV (Figure b), which is smaller than pristine 7‐ AGNR . 7‐ AGNRs with −CN functional groups edge modification induce a downshift on the ribbon bands of ∼0.3 eV per −CN added (Figure c and Figure d) . Besides, edge‐fluorinated 7‐ AGNRs have been predicted to reveal electronic properties .…”
Section: Tuning the Electronic Propertiesmentioning
confidence: 99%
“…(b) The corresponding dI/dV spectra of 7‐ phenyl‐GNRs . (c) Constant height dI/dV image with a CO‐functionalized tip, Red arrows mark the positions of the CN groups . (d) Corresponding dI/dV spectra in colored crosses mark the position of (c).…”
Section: Tuning the Electronic Propertiesmentioning
confidence: 99%